Legal politics of blasphemy in religion in Rudolf Stammler's perspective - Sholehudin, Miftahus (Faculty of Law, University of Muhammadiyah Malang, 2020)
The conflict based on religion is a very sensitive issue in various countries of the world. Indonesia as a godly state as contained in the state philosophy of the first precepts Pancasila has also given birth to special regulations in dealing with the defamation problem contained in Law No. 1 PNPS 1965. Using a historical approach, this legal research uses a type of normative legal research. Rudolf Stamler's theory, which became the knife of analysis in this study, showed that the blasphemy law was formed with a repressive pattern in which the state with its power to make laws and regulations forced both politically and legally. However, the presence of repressive law is the most appropriate solution when viewed from the historical record of the conflict in Indonesia which is motivated by the issue of religion. So that under the ideals of the law, the accuracy of the legislation at that time should be adjusted to the conditions of the nation to create a law that is responsive and fair